Influence of Tuber Seed Size on Susceptibility of Cipira Potato Variety to Aphid (Myzus persicae), and Potato Blight and Bacterial Wilt Diseases - Achiri, Tange Denis; Tabi, Oben Tom; Leke, Tawung Brayand; Bi, Manju Evelyn; Nsobinenyui, Divine; Tatah, Lendzemo Eugene; Njualem, Khumbah Dominic (Fundamental and Applied Agriculture, 2024)
Potato (Solanum tuberosum L.) is one of the most important tuber crops in the world and it is fourth among food crops after rice, wheat and maize. Potato is widely cultivated for its cheap source of carbohydrates, vitamins as well as minerals. In Cameroon where potato provide a livelihood for most producers, especially in the Western highland, production is challenged by unavailability of appropriate seeds of local varieties or Cameroon improve varieties. Many decades ago, Cipira was released by the Institute of Agricultural Research for Development, Bambui, North West Region, Cameroon as an improved resistant variety. The current study evaluated the performance of Cipira considering seed sizes. Four seed sizes (20mm, 25mm, 30mm and 35mm diameter) were evaluated in a randomized complete block trial in Bambili in 2022 and 2023. Green peach aphid incidence was inversely related to tuber seed sizes (P < 0.05). Aphid population abundance was higher from plants with larger diameter. Late blight and bacterial wilt incidence and disease severity index was significantly higher for plants of smaller tuber seed size. Productivity was 8.06 t ha-1, 6.2 t ha-1, 5.7 t ha-1 and 5.8 t ha-1 from 35mm, 30mm, 25mm and 20mm tuber seed sizes, respectively in 2022. The yield in 2023 was 8.9 t ha-1, 7.8 t ha-1, 7.1 t ha-1 and 6.3 t ha-1 from 35mm, 30mm, 25mm and 20mm, respectively. For improved yield and reduced pest and diseases incidences, Cipira at 30 mm and 35 mm seed sizes are recommended.